Development Of Inquiry-Based Student Worksheets (Lkpd) To Improve Economics Learning Outcomes In Students Of Class Xi Ips 1 Sma Negeri 2 Padang Cermin - Duri, Anggun Rafika; Saryantono, Buang; Mahrunnisya, Dyanti (FKIP Universitas Lampung, 2023)
The problems contained in this study are motivated by 1) low learning outcomes, 2) economic learning that has been implemented so far has not used teaching materials in the form of LKPD, 3) the learning process pays little attention to the condition of students in terms of abilities, talents, interests and needs, so that student learning outcomes are still low. The purpose of this study was to determine the level of validity, level of attractiveness, convenience and usefulness as well as the level of effectiveness of the development of inquiry-based worksheets to improve economic learning outcomes in KD. describes the international trade of class XI IPS 1 students of SMA Negeri 2 Padang Cermin. This research is a type of research and development, this research is used to produce certain products and test the effectiveness of these products. The resulting product is an inquiry-based LKPD in economics subjects to determine product validation, attractiveness, convenience and usefulness as well as the effectiveness of LKPD which will be developed in improving learning outcomes. The stages of the research carried out refer to the ADDIE development model which includes Analysis, Design, Development, Implementation and Evaluation. The results showed that the level of effectiveness of students' learning outcomes from this LKPD was also very good because it had a completeness percentage of 90.90% so that it showed very good student learning outcomes. So it can be concluded that the development of inquiry-based LKPD is very feasible to be developed in class XI IPS 1 students of SMA Negeri 2 Padang Cermin.Keywords: Development, Inquiry, Student WorksheetsDOI: http://dx.doi.org/10.23960/E3J/v6i2.145-152